(untitled) (Journal of Parents and Teachers, 2014)
Alcohol causes physical and psychological problems, family and social problems, work and domestic problems and violent behavior. It is necessary to distinguish between addiction and illness, although the harmful effects will be caused in both cases, though to a greater or lesser extent. Therefore, this article focuses on these effects and on prevention methods to avoid them.